Durability of immune response after SARS-CoV-2 vaccination in patients with chronic liver disease - Song, Ruixin; Yang, Chao; Li, Qianqian; Wang, Jiayin; Chen, Jing; Sun, Kai; Lv, Hongmin; Yang, Yankai; Liang, Jing; Ye, Qing; Gao, YanYing; Li, Jun; et al. (Frontiers in Immunology, 2023)
Abstract Aim: The present study aimed to evaluate the durability of immune response after basic and booster immunization with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines in patients with chronic liver disease (CLD). Methods: Patients with CLD and complete basic or booster immunization with SARS-CoV-2 vaccines were included in this study. Based on the vaccination situation, they were divided into basic immunity group (Basic) and booster immunity group (Booster), which were then subdivided into four groups according to the time interval from completion of basic immunization or booster immunization to serological specimen collection. The positive rates and antibody titers of novel coronavirus neutralizing antibody (nCoV NTAb) and novel coronavirus spike receptor-binding domain antibody (nCoV S-RBD) were analyzed. Results: A total of 313 patients with CLD were enrolled in this study, including 201 in Basic and 112 in Booster. The positive rates of nCoV NTAb and nCoV S-RBD within 30 days of completing basic immunization were 80.4% and 84.8%, respectively, but decreased rapidly with the extension of vaccination time, and only 29% and 48.4% of patients with CLD remained positive for nCoV NTAb and nCoV S-RBD, respectively, after 120 days of completing basic immunization. Within 30 days of booster immunization, the positive rates of nCoV NTAb and nCoV S-RBD in patients with CLD rapidly increased from 29.0% and 48.4% at the end of basic immunization to 95.2% and 90.5%, and maintained a high level (defined as the positive rate >50%) until 120 days when the positive rates of nCoV NTAb and nCoV S-RBD were still high at 79.5% and 87.2%, respectively. After basic immunization, the time for nCoV NTAb and nCoV S-RBD to turn negative was 120 and 169 days, respectively, and the negative time of nCoV NTAb and nCoV S-RBD was significantly prolonged to 266 days and 329 days, respectively. Conclusion: It is safe and effective for patients with CLD to complete basic and booster immunization with SARS-CoV-2 vaccines. After booster immunization, immune response of patients with CLD was further improved and durability of SARS-CoV-2 antibody was significantly prolonged.